In Vitro Micropropagation of Noni (Morinda citrifolia L.) through Nodal Segments and Shoot Tips Culture (Journal of Bio-Science, 2026)
The present study was conducted to develop an efficient in vitro micropropagation protocol for Noni, an important medicinal plant, using nodal segments and shoot tips. In this study the Murashige and Skoog medium was considered with various concentrations and combinations of BAP and Kinetin. For the evaluation of shoot and root induction, their proliferation and the increased number of shoots and roots, various auxins (IBA, IAA and NAA) were used. The highest length of shoots (5.2 0.15 cm) and the highest number of shoots (3.2 0.13) were found on MS medium supplemented with BAP (4.0 mg/l) and Kinetin (2.0 mg/l) from nodal segments. In this case a data were recorded after 12 weeks of culture initiation. After 42 days, the highest number of roots per shoot (32.5 0.40), the highest length of roots (1.9   0.07 cm) and percent of shoots (86.0%) induced roots were recorded on half strength (½) MS medium containing IBA (2.0 mg/l). The aftermaths of this study showed that nodal segments were better explants than shoot tips for the in vitro micropropagation of Noni.J. Bio-Sci. 33(2): 43-50, 2025